A Brief Report on the Explosion on 13 June 2021 at a Market in Shiyan, China - Zhe-Han Wang; Pierre Guy Atangana Njock; Lin-Shuang Zhao (Safety, 2021)
A huge gas explosion occurred on 13 June 2021 in Shiyan City, China, resulting in 25 casualties and serious injuries to 37 people. The main victims of this explosion were stall keepers and customers buying breakfast and fresh vegetables in the food market. There is a continuous need to enhance the understanding of such unfortunate events, given the dangers they pose. This study analyzes the causes of this accident considering the general background and scenes of the explosion, and then describes the rescue operations undertaken. The investigation results revealed that the explosion was caused by the poor maintenance of gas facilities and negligence of safety regulations. It is, therefore, recommended that the control of these two main aspects be strengthened to reduce the recurrence of such unfortunate accidents.